Increased apoptotic sensitivity of glioblastoma enables therapeutic targeting by BH3-mimetics - Koessinger, Anna L.; Cloix, Catherine; Koessinger, Dominik; Heiland, Dieter Henrik; Bock, Florian J.; Strathdee, Karen; Kinch, Kevin; Martínez-Escardó, Laura; Paul, Nikki R.; Nixon, Colin; Malviya, Gaurav; Jackson, Mark R.; et al. (Cell Death and Differentiation, 2022)
Glioblastoma (GBM) is the most prevalent malignant primary brain tumour in adults. GBM typically has a poor prognosis, mainly due to a lack of effective treatment options leading to tumour persistence or recurrence. We investigated the therapeutic potential of targeting anti-apoptotic BCL-2 proteins in GBM. Levels of anti-apoptotic BCL-xL and MCL-1 were consistently increased in GBM compared with non-malignant cells and tissue. Moreover, we found that relative to their differentiated counterparts, patient-derived GBM stem-like cells also displayed higher expression of anti-apoptotic BCL-2 family members. High anti-apoptotic BCL-xL and MCL-1 expression correlated with heightened susceptibility of GBM to BCL-2 family protein-targeting BH3-mimetics. This is indicative of increased apoptotic priming. Indeed, GBM displayed an obligate requirement for MCL-1 expression in both tumour development and maintenance. Investigating this apoptotic sensitivity, we found that sequential inhibition of BCL-xL and MCL-1 led to robust anti-tumour responses in vivo, in the absence of overt toxicity. These data demonstrate that BCL-xL and MCL-1 pro-survival function is a fundamental prerequisite for GBM survival that can be therapeutically exploited by BH3-mimetics.
CRIS-Team Scopus Importer:2023-09-13